voorbeeld 1

Rekenregels voor logartimen

Hoofdregel: $
{}^g\log (x) = y \Leftrightarrow g^y = x
$

Hieruit volgt: $
g^{{}^g\log (x)} = x
$

Daarmee kan je de volgende regels aantonen:

$
\begin{array}{l}
{}^g\log (a) + {}^g\log (b) = {}^g\log (ab) \\
{}^g\log (a) - {}^g\log (b) = {}^g\log (\frac{a}{b}) \\
n \cdot {}^g\log (a) = {}^g\log (a^n ) \\
 {}^g\log (a) = \large\frac{{{}\log (a)}}{{{}\log (g)}} \\
\end{array}
$

Voorbeeld 1

$
\begin{array}{l}
5 + 3 \cdot {}^2\log (3) - {}^2\log (100) = \\
{}^2\log (2^5 ) + {}^2\log (3^3 ) - {}^2\log (100) = \\
{}^2\log \left( {\frac{{32 \cdot 27}}{{100}}} \right) = {}^2\log \left( {8\frac{{16}}{{25}}} \right) \\
\end{array}
$

©2004-2021 Wiskundeleraar - login